PWE-026 Effects of 26 Weeks of Linaclotide Treatment on Adequate Relief and IBS Severity in Patients with Irritable Bowel Syndrome with Constipation (IBS-C). (4th June 2013) - Quigley, E M; Chey, W D; Lavins, B; Baird, M; Fitch, D; Hao, X; Shi, K; Currie, M; Schneier, H; Johnston, J
Abstract : Introduction: There have been few long-term studies evaluating treatments for IBS. Linaclotide (LIN), a 14 amino acid, minimally absorbed, guanylate cyclase C agonist (GCCA), was evaluated in 2 Phase 3 trials in patients (pts) with IBS-C, including a double-blind trial with an extended 26 wk Treatment Period, in which statistically significant improvements in abdominal pain and complete spontaneous bowel movement (CSBM) frequency were sustained for up to 26 wks. In a subsequent analysis of this study, we assessed the effects of 26 wks of LIN treatment on adequate relief and IBS severity and the relationship between long-term improvement in adequate relief with improvements in abdominal pain and CSBM frequency. Methods: Adult pts with IBS-C (Rome II criteria) were randomised to LIN 290 μg or placebo (PBO) qd po for 26 wks. Endpoints included daily pt rating of abdominal pain at its worst during the previous 24 h on an 11-point scale (0 = none, 10 = very severe) and CSBM frequency. Pts also rated adequate relief of IBS symptoms (yes/no) and IBS severity (5-point scale: 1 = none, 5 = very severe) weekly. An Adequate Relief Responder was defined as a pt with adequate relief of IBS symptoms for ≥13 of the 26 wks of the Treatment Period. Spearman correlations were performed for Adequate Relief Responders and individual symptom improvement. Results: The study included 401 LIN- and 403 PBO-treated pts. With LIN, 49% of pts were Adequate Relief Responders vs 25% of PBO pts (difference 24.1; p < 0.0001; No. needed to treat 4.2). For 26 Wk IBS severity: 48% of LIN pts rated IBS severity as "none/mild" vs 26% of PBO pts (Table). In all pts, Adequate Relief Responders had a 26-wk mean decrease in abdominal pain of 52% vs 18% for nonresponders and an increase from baseline in 26-wk mean CSBM frequency of 3.0/wk vs 0.8/wk for nonresponders. Improvements in abdominal pain (r = 0.48) and CSBM frequency (r = 0.53) correlated with adequate relief. Conclusion: Significantly more LIN pts vs PBO pts reported adequate relief of IBS symptoms and improvement of IBS severity during 26 wks of treatment. Gains in the % of pts reporting adequate relief correlated strongly with improvements in abdominal pain and CSBM frequency. Supported by Ironwood Pharmaceuticals Inc and by Forest Laboratories Inc. Editing assistance was provided by Complete Medical Communications, funded by Almirall. Disclosure of Interest: E. Quigley Speaker bureau with: Danone, Janssen, Procter and Gamble, sanofi-aventis, Shire and Yakult, Conflict with: Advisory boards for Almirall, Ironwood, Janssen, Norgine, Salix and Shire/Movetis, W. Chey Consultant for: Ironwood Pharmaceuticals and Forest Research Institute, B. Lavins Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, M. Baird Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, D. Fitch Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, X. Hao Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, K. Shi Employee of: Forest Laboratories, M. Currie Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, H. Schneier Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, J. Johnston Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals